PENGARUH ELECTRONIC WORD OF MOUTH DAN TOURIST MOTIVATION TERHADAP SATISFACTION SERTA REVISIT INTENTION - Aitarra, Galang; Pujiastuti, Eny Endah; Nur Utomo, Hastho Joko (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
Revisit intention in tourism marketing is the hope of destination managers for the sustainability of their destinations. Revisit intention of tourist areas is influenced by many factors. The problems and objectives of this study are the effect of electronic word of mouth and tourist motivation on satisfaction and revisit intention. The research location is on the beach of Krakal Gunung Kidul, Yogyakarta. Tourists who have visited the destination for the first time become the research samples. The data collected from 120 respondents with questionnaires, dan analyzed by SEM AMOS. The conclusion of this study shows that electronic word of mouth and also tourist motivation have a significant effect on satisfaction, electronic word of mouth has a significant effect on revisit intention, either on tourist motivation too, also there was a significant effect from satisfaction on revisit intention. The limitation of this study which the sample criteria is to general, it is need more specific, such as by age, then the bias will be more minimize. Further research hoped that it can examine other variables like attractiveness, facilities and tourist experience.